Elevating Lexical Proficiency: Enhancing Students' Vocabulary Mastery with English Spelling Bee Challenges - Aras, Rahmalia Putri; Hastini, Hastini (Journal of General Education and Humanities, 2024)
This study aims to determine if spelling bee competitions aid in vocabulary growth for SMP Negeri 3 Banawa class VIII students. This study uses a quasi-experimental research approach using both controlled and experimental categories. Purposive sampling was used to choose the sample. Class VIII A has twenty-four students, while Class VIII B and the control class also have twenty-four students. Vocabulary tests were administered both before and after therapy to gather data. There is a pre-test and a post-test for the test. The control class received 39.27 points, whereas the experimental class had an average projected score of 50.83. The experimental class's post-test score was 73.63, whereas the control group scored 49.86. The data analysis findings indicate α = 0.05 and Sig. (2-tailed) based on the t-test, the predicated equality between the two means is 0.000. Sig.(2-tailed) < α = 0.05. in light of this. Ho was turned down, while Ha was accepted. Calculations show that SMP Negeri 3 Banawa class VIII students' vocabulary mastery has increased dramatically due to using the English Spelling Bee.